A Br− anion adsorbed porous Ag nanowire film: in situ electrochemical preparation and application toward efficient CO2 electroreduction to CO with high selectivity. Issue 9 (16th July 2018) - Qiu, Weibin; Liang, Ruping; Luo, Yonglan; Cui, Guangwei; Qiu, Jianding; Sun, Xuping
Abstract : An AgBr-derived porous Ag nanowire film with adsorbed Br − anions shows a low onset overpotential of only 296 mV and a high CO faradaic efficiency of 96.2% at −0.6 V in CO2 -saturated 0.5 M KHCO3 . Abstract : Developing selective and cost-effective CO2 reduction electrocatalysts is critical for electrochemical production of carbon-containing fuels. In this communication, we report on the in situ fabrication of a bromide-derived porous Ag nanowire film (BD-Ag) with adsorbed Br − anions via anodic oxidation of commerical Ag foil and subsequent electrochemical reduction. The resulting BD-Ag behaves as an efficient electrocatalyst for CO2 reduction to CO with high selectivity, with a low onset overpotential of only 296 mV and a high CO faradaic efficiency of 96.2% in 0.5 M KHCO3 . Furthermore, it also shows excellent long-term electrochemical durability. This work offers an attractive catalyst material toward efficient and selective CO2 reduction for electrocatalytic applications.